ADVANCED MATERNAL AGE AND PREVALENCE OF CHROMOSOMAL ABNORMALITIES IN CASES OF DISORDERS OF SEX DEVELOPMENT (DSD) - Anushree Pandey; Dewanshi Mishra; Rakesh Kumar Verma; Archana Rani; Navneet Kumar; S.N. Singh; Sudhir Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Disorders of Sex Development (DSD) encompass a diverse group of congenital conditions in which the development of chromosomal, gonadal, or anatomical sex is atypical. While DSDs are primarily genetic or sporadic in origin, emerging evidence suggests that advanced maternal age (AMA) may influence the prevalence and expression of chromosomal abnormalities in DSD cases. This review explores the association between AMA and chromosomal anomalies contributing to DSDs, with an emphasis on meiotic nondisjunction, sex chromosome aneuploidy, and diagnostic implications in the prenatal and neonatal period.